2008
DOI: 10.1007/s00330-008-1200-x
|View full text |Cite
|
Sign up to set email alerts
|

Glenohumeral joint injection: a comparative study of ultrasound and fluoroscopically guided techniques before MR arthrography

Abstract: To assess the variability in accuracy of contrast media introduction, leakage, required time and patient discomfort in four different centres, each using a different image-guided glenohumeral injection technique. Each centre included 25 consecutive patients. The ultrasound-guided anterior (USa) and posterior approach (USp), fluoroscopic-guided anterior (FLa) and posterior (FLp) approach were used. Number of injection attempts, effect of contrast leakage on diagnostic quality, and total room, radiologist and pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
77
1
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(85 citation statements)
references
References 23 publications
5
77
1
2
Order By: Relevance
“…Furthermore, no difference was detected at first entry in fluoroscopic injection Many studies indicate that superior and earlier improvement in shoulder pain and increased range of motion in the shoulder joint are possible with US-guided injections compared to blind injections. [2,5,14] In our study, clinically improved pain was observed in all patients except one. Decrease in VAS scores continued for one month.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Furthermore, no difference was detected at first entry in fluoroscopic injection Many studies indicate that superior and earlier improvement in shoulder pain and increased range of motion in the shoulder joint are possible with US-guided injections compared to blind injections. [2,5,14] In our study, clinically improved pain was observed in all patients except one. Decrease in VAS scores continued for one month.…”
Section: Discussionsupporting
confidence: 65%
“…[13] In another study, Ucuncu et al [5] compared US with landmark-guided injection in a randomized study and demonstrated significantly improved pain intensity in US group compared with blind group six weeks after injection (mean VAS score decrease: 4.0±1.7 for US vs. 2.2±0.9 for blind). Rutten et al [14] compared FL with US-guided intra-articular shoulder injections and reported 76% accuracy in FL and 96% in US on the first attempt using an anterior approach.…”
Section: Discussionmentioning
confidence: 99%
“…This is now a relevant issue for physiotherapists as many working in an extended scope role in the NHS are now performing injections. It has been documented that 14-71% of injections carried out ''blind''-without image guidance-miss their target [23][24][25][26][27]. What we do not know is whether this makes a difference in clinical efficacy.…”
Section: Ultrasound-guided Injectionsmentioning
confidence: 99%
“…Altogether these findings reflect the importance of a imaging-guided method for glenohumeral joint injections. 35,36) Gokalp et al 37) reported that injections from the posterior side of the patient is more favorable than from the anterior side where important structural elements such as the glenohumeral ligament may get in the way. Agreeing with Gokalp et al's findings, 37) authors too made the injection from the posterior side of the patient.…”
Section: Medial Lateralmentioning
confidence: 99%